Disclosure practices of corporate social responsibility and firm financial performance: a study of listed banks in sri lanka. - Panuja, E.; Arulvel, K. (University of Jaffna, 2019)
This study examines the disclosure practices of Corporate Social Responsibility (CSR) and firm financial performance of listed banks in Sri Lanka over the period of 2013-2017. A population of all 13 banks listed under Bank, Finance, and Insurance sector of CSE Sri Lanka was studied. The study made use of secondary data gathered from annual reports of banks. The data is analyzed by correlation and regression analysis using STATA (version 12) package. The result of regression analysis suggests that disclosure practices of corporate social responsibility significantly affect the Return on assets (ROA) of banks. And also disclosure practices of corporate social responsibility does not significantly affect Tobin’s Q. Correlation analysis indicates that disclosure practices of corporate social responsibility have significant negative relationship with ROA while Tobin’s Q has an insignificant positive relationship.
Keywords: Disclosure practices of corporate social responsibility; Return on assets (ROA); Tobin’s Q